Computing and communication - Vijayakumar, R. (Narosa, 2012)
COMPUTING AND COMMUNICATION gives a glimpse of the selected research areas of interesting topics in the subject of computing and communication, relating to Data Mining, Information Security, Image Processing and Signal Processing and guides you through the progress in the fields like, Dynamic Address Routing, Measure for Web Page Similarity, Delay Minimization Techniques in Anonymity Networks, An enhanced FP-Tree Algorithm in large Database Mining, Moving Object Database Handling, Web Characterization, Efficient Consistency maintenance and Load Flow studies by Parallel Computation. Moreover it deals with the Intellectual Property protection, Multimedia content protection, applying two-stage FEC scheme, performance prediction of string algorithms, Nonlinear channel equalization in Communication, User story validation and Location Privacy in mobile systems. This volume is a road map showing the position of Image Processing areas like Hand-written text recognition, Image classification using wavelet decomposition, Performance evaluation of string algorithms, Multi Human Tracking and Adaptive Median Filter designing.